Outcomes of Open Reduction and Internal Fixation of Bilateral Fractures of the Distal Radius - Graham, Jack G.; Penna, Sreeram; Fletcher, Daniel; Kwok, Moody; Aita, Daren J.; Takei, T. Robert; Beredjiklian, Pedro K. (Journal of Hand and Microsurgery, 2019)
Background Bilateral distal radius fracture (DRF) is an uncommon injury. We described the outcomes of 10 consecutive cases of bilateral DRF treated with open reduction and internal fixation (ORIF) at our institution.Materials and Methods We retrospectively searched our electronic medical records data for all patients 18 years of age or older treated surgically for bilateral DRF over a 6-year period (2011–2016). Patient demographics, fracture classification, fixation method, postoperative complications, QuickDASH (Quick Disabilities of the Arm, Shoulder and Hand) questionnaire scores, wrist range of motion (ROM), and radiographic measurements of X-rays at final follow-up were collected and analyzed.Results Ten patients (8 women; 2 men; mean age: 63 years) with 20 fractures were assessed. A volar approach for ORIF was used in 90% of cases. Six of 20 (30%) wrists experienced postoperative complications and required hardware removal. Mean QuickDASH score was 24.8 at final follow-up. On average, ROM reached 58-degree extension, 52-degree flexion, 75-degree pronation, and 75-degree supination. Mean measurements of radial shortening, radial inclination, and volar tilt taken from final postoperative radiographs were 1.3 mm, 21.2 degrees, and 7.8 degrees, respectively.Conclusion In bilateral DRF treated with concomitant ORIF, functional outcomes, recovery of wrist ROM, and restoration of radiographic parameters are comparable to those seen in patients with ipsilateral DRF.
Keywords: distal radius; fracture; bilateral; wrist trauma; fixation; volar plating; outcomes; recovery; complications